Dakwah Islam dalam Masyarakat Abangan: Analisis Sejarah dan Sosial di Desa Sidomulyo, Kecamatan Bakung, Kabupaten Blitar - Muslim, Ahmad Shobiri; Mujab, Saiful (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aims to investigate the dynamics of Islamic propagation within the Abangan community, focusing on Sidomulyo Village, Bakung Subdistrict, Blitar Regency. The Abangan community, characterized by its retention of animistic and syncretic traditions, presents unique challenges to Islamic preachers in disseminating religious teachings. Employing a historical and social analysis approach, this research delves into the hurdles encountered by Islamic preachers and the strategies they employ to engage with the Abangan community. Data collection involved observation, interviews, and literature review. Findings reveal that the process of Islamic propagation in Sidomulyo Village encounters obstacles, including the persistence of non-Islamic traditions and the historical complexity of the area as a former PKI stronghold. Nonetheless, Islamic preachers, notably those affiliated with Lirboyo Islamic Boarding School, have embraced the approach of da'wah bil-hikmah (wise preaching), characterized by patience, composure, and cultural adaptation. Despite the community's strong adherence to Abangan traditions, such as Jaranan, Karawitan, slametan, tayuban, and ritual practices, through Kyai Syahson's meticulous Islamic proselytization efforts, gradual acceptance of Islamic teachings and abandonment of conflicting practices have been observed. These efforts faced challenges, including spiritual interferences, financial limitations, Kyai Syahson's status as a newcomer, and the entrenched Abangan culture. Nevertheless, through patience, resilience, and adaptation, Kyai Syahson successfully instigated significant transformations in the religious beliefs and practices of the Sidomulyo community.